Influence of ruminal methane on digesta retention and digestive physiology in non-lactating dairy cattle. Issue 5 (25th July 2016) - Dittmann, Marie T.; Hammond, Kirsty J.; Kirton, Paul; Humphries, David J.; Crompton, Les A.; Ortmann, Sylvia; Misselbrook, Tom H.; Südekum, Karl-Heinz; Schwarm, Angela; Kreuzer, Michael; Reynolds, Christopher K.; Clauss, Marcus
Abstract: Enteric methane (CH4 ) production is a side-effect of herbivore digestion, but it is unknown whether CH4 itself influences digestive physiology. We investigated the effect of adding CH4 to, or reducing it in, the reticulorumen (RR) in a 4×4 Latin square experiment with rumen-fistulated, non-lactating cows, with four treatments: (i) control, (ii) insufflation of CH4 (iCH4 ), (iii) N via rumen fistula, (iv) reduction of CH4 via administration of bromochloromethane (BCM). DM intake (DMI), apparent total tract digestibility, digesta mean retention times (MRT), rumen motility and chewing activity, spot breath CH4 emission (CH4 exhal, litre/kg DMI) as well as CH4 dissolved in rumen fluid (CH4 RRf, µg/ml) were measured. Data were analysed using mixed models, including treatment (or, alternatively, CH4 exhal or CH4 RRf) and DMI relative to body mass 0·85 (rDMI) as covariates. rDMI was the lowest on the BCM treatment. CH4 exhal was highest for iCH4 and lowest for BCM treatments, whereas only BCM affected (reduced) CH4 RRf. After adjusting for rDMI, CH4 RRf had a negative association with MRT in the gastrointestinal tract but not in the RR, and negative associations with fibre digestibility and measures of rumination activity. Adjusting for rDMI, CH4 exhal had additionally a negative association with particle MRT in the RR and a positive association with rumen motility. Thus, higher rumen levels of CH4 (CH4 exhal or CH4 RRf) were associated with shorter MRT and increased motility. These findings are tentatively interpreted as a feedback mechanism in the ruminant digestive tract that aims at mitigating CH4 losses by shortening MRT at higher CH4 .